Energy, Economic, and Environmental Performance of Commercial Water Heating Systems. Issue 4 (19th August 2014) - To, W.M.; Hung, H.K.; Chung, W.L.
Abstract : Purpose: The purpose of this paper is to evaluate the energy, economic, and environmental performance of commercial water heating systems in Hong Kong SAR, China. Design/methodology/approach: The research team contacted 50 facilities managers in Hong Kong and 16 of them agreed to participate in this territorial-wide survey. The overall efficiency of different water heating systems was determined through measurements of inlet water temperatures, outlet steam/water properties, the amount of steam/water produced, and the amount of energy consumed. The cost effectiveness and the amount of greenhouse gases produced per MJ output were also determined. Findings: Results show that electric water heating systems had the highest mean overall efficiency, followed by gas-fired systems and oil-fired systems. However, the difference between the mean overall efficiency of the three types of water heating systems was not statistically significant as the systems had been inspected and maintained regularly. Oil-fired systems were found to be the most cost effective when taking fuel prices into consideration. Environmental analysis showed that gas-fired systems produced the least amount of greenhouse gases per MJ output. Originality/value: Water heating is one of the major uses of energy in buildings. Hence, the efficiency of a water heating system can have a significant effect on the overall performance of a building. This paper not only provides insight on the energy performance, it also evaluates the economic and environmental performance of water heating systems.